مروجہ نظامِ ٹیکس کا شرعی تناظر میں ایک جائزہ: An overview of the prevailing taxation system in Shariah perspective - Dr. Salman Ahmad Khan; Dr. Shamsul Arifeen (International Research Journal of Arabic and Islamic Studies, 2024)
Taxation has always been a topic of debate. There have been both opinions in this regard. This article examines the extent to which tax collection is permissible in a Shariah and historical context. Discussion in this article shows that taxation is not primarily related to the economic system of Islam. There are both types of opinions regarding the legitimacy and illegitimacy of taxes, but in unavoidable situations, the opinions of legitimacy can be followed by considering the conditions of it. In the current tax system, this responsibility is especially for businessmen that they should pay legitimate taxes so that the burden of non-payment does not fall on the poor and middle class with fixed incomes. Governments should adopt a fair attitude towards taxation, in our country, the prevailing tax rates are too high compared to the facilities provided and the rates do not match (within the level of justification) the teachings of Sharia. Therefore, governments need to revise the prevailing tax policies. Luxury, greed, nepotism, intolerance for the public and lack of foresight are the main factors that induce the rulers to oppress the people, one of the major forms of which is the collection of oppressive taxes.